1968
DOI: 10.1507/endocrj1954.15.313
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Concentrations in Pituitary and in Blood Plasma During the Estrous Cycle of the Rat

Abstract: SYNOPSISSimultaneous measurement of luteinizing hormone (LH) in the pituitary and in circulating blood is a necessary step for the determination of its storage and secretion patterns during the estrous cycle, by which the critical time of preovulatory surge of LH would be determined. Since a sensitive and specific assay method for LH, the ovarian ascorbic acid depletion test, was established by Parlow (1958Parlow ( ,1961, the changes in pituitary LH content during the estrous cycle were determined by Mills a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
1

Year Published

1969
1969
1981
1981

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 4 publications
6
37
1
Order By: Relevance
“…This corresponds with the results reported by Eto et al(1962) and Hashimoto et al(1968). Figure 6 illustrates a chronologic relation of the pattern of preovulatory increase of progesterone secretion to the patterns of estrogen secretion (Hori et al, 1968) and plasma LH concentration (Kobayashi et al, 1968) and to the timing of ovulation (Kobayashi et al, 1968) in the 4-day cyclic rats of the same strain bred under the same lighting schedule (12 hrs. light, 8 a.m. to 8 p.m.), the outline of which was reported in a proceeding form (Miyake, 1968).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This corresponds with the results reported by Eto et al(1962) and Hashimoto et al(1968). Figure 6 illustrates a chronologic relation of the pattern of preovulatory increase of progesterone secretion to the patterns of estrogen secretion (Hori et al, 1968) and plasma LH concentration (Kobayashi et al, 1968) and to the timing of ovulation (Kobayashi et al, 1968) in the 4-day cyclic rats of the same strain bred under the same lighting schedule (12 hrs. light, 8 a.m. to 8 p.m.), the outline of which was reported in a proceeding form (Miyake, 1968).…”
Section: Discussionsupporting
confidence: 88%
“…Chronologic relation of preovulatory secretion of progesterone to estrogen secretion, LH release and ovulation (Hori et al, 1968;Kobayashi et al, 1968). ing blood is undetectable (Kobayashi et al, 1968), and further, the same grade of increased secretion rates at this time is manifested even in the rats hypophysectomized on the morning of the day of early diestrus or on the afternoon of the day of estrus. This concept is supported by the in vitro experiments of Chatterton et al (1968), who have demonstrated that the rat ovarian tissue at any stage of the cycle is able to synthesize a considerable amount of progesterone and 20a-OH-P in the medium without LH and the incorporation of acetate-1-14 C into progesterone and 20a-OH-P is not affected by LH, whereas the incorporation of acetate into both progestins is markedly higher during the luteal phase.…”
Section: Discussionmentioning
confidence: 97%
“…1). This coincides with the time of LH release from the pituitary which has been determined by Kobayashi et al (1968) using the same laboratory rats bred under the same conditions. This fact suggests that the increase of progesterone at proestrus is caused by LH, since there are evidences that LH causes an increase in rat ovarian progesterone synthesis in vivo (Marsh et al, 1966;Yoshinaga et al, 1967) and in vitro (Armstrong and Greep, 1962;Armstrong et al, 1964;Channing and Villee, 1966;Major et al, 1967;Chatterton et al, 1968).…”
Section: Discussionsupporting
confidence: 79%
“…The determination of ovarian progestin secretion and plasma LH level on the same laboratory rats bred under the same condition (Miyake, 1968;Kobayashi et al, 1968;Uchida et al, 1969) has demonstrated that the increase in progesterone secretion at proestrus occurs almost concurrently with an increase in plasma LH level. Furthermore, hypophysectomy at 5.00p.m.…”
mentioning
confidence: 99%
“…The LH content in the pituitary is already high during the morning of proestrus before the critical period (Schwartz and Bartosik, 1962;Anderson and McShan 1966;Kobayashi et al, 1968;Monroe et al, 1969), but it is not released until afternoon, although Zeilmaker (1966), Nallar et al (1966), Redmond (1968) and Brown-Grant (1967) showed an enhancement of LH release by progesterone several hours before the critical period. Progesterone delays the critical period, eventually ovulation, if it is given about 20 hr before, on the afternoon of diestrus II (Zeilmaker 1966;Caligaris et al, 1968).…”
Section: Synopsismentioning
confidence: 95%